Physical activity and heart failure: a forgotten indicator. (3rd October 2022) - Barradas, M; Duarte, F; Coutinho Dos Santos, I; Resendes De Oliveira, L; Serena, C; Xavier Fontes, A; Viveiros Monteiro, A; Machado, C; Dourado, R; Santos, E; Pelicano, N; Pacheco, M; et al.
Abstract: Introduction: Low physical activity may be associated with comorbidities, sedentary lifestyle or clinical worsening in heart failure (HF) patients. Cardiovascular implantable electronic devices (CIEDs) detect and analyse physical activity data that is often integrated in multifactorial algorithms for predicting HF decompensations, but its potential is probably underestimated. Purpose: We hypothesized that low physical-activity levels, obtained from remote monitoring of CIEDs, help predict clinical outcomes in HF patients, independently from multifactorial algorithms. Methods: We retrospectively evaluated consecutive patients with HF and CIEDs through clinical assessments and remote monitoring (two monitoring systems were used). Low activity was defined as <1 hour/day of physical activity and two groups of patients were defined: patients with low activity alerts (group 1) and patients without low activity alerts (group 2). Primary outcome was defined as death by all causes and secondary outcome as HF hospitalizations and sustained ventricular tachycardia (VT) or ventricular fibrillation (VF) episodes. Results: From 121 patients with RPM, physical activity data was obtained in 104 (85, 9%). Mean age was 63, 98±12, 44 years, 70, 2% were males and follow-up was 59, 19±38, 491 months. Fifty-four (51, 9%) had implantable cardiac resynchronization therapy (CRT) defibrillator (CRT-D), 46 (44, 2%) transvenous implantable cardioverter defibrillator (ICD), and 4 (3, 8%) CRT pacemaker (CRT-P). The aetiology was idiopathic in 42, 5% and ischemic in 40, 2%. Mean left ventricular ejection fraction was 34, 08±11, 40% and mean physical activity duration was 2, 25±1, 84 hours/day. Forty-eight (53, 7%) had low activity alerts (group 1) and 56 (46, 3%) had no low activity alerts (group 2). In group 1 mean period of low activity was 52, 978±15, 75 days/year. Patients from group 1 were older (p=0, 001), had more oncological disease (p=0, 041) and peripheral artery disease (p=0, 028). Three deaths occurred in total, all in group 1 (p=0, 039) and HF hospitalizations were more frequent in group 1 (1, 68±2, 59 vs 0, 69±1, 32, p=0, 005). Low activity burden was also associated with atrial fibrillation burden (r=0, 473, p<0, 05) and number of episodes of VT or VF (r=0, 267, p=0, 007). A decrease of 50% or more in mean duration of physical activity, but above 1 hour/day, was associated with increase HF hospitalizations (1, 83±2, 13 vs 1, 05±1, 95, p=0, 006). Conclusion: Low physical activity data obtained from CIEDs was associated with HF hospitalizations, arrhythmic events and death by all causes, independently of multifactorial algorithms. A decrease in basal activity even above alert threshold, was associated with HF hospitalizations and may be an even earlier sign of HF decompensations. Funding Acknowledgement: Type of funding sources: None.